Pengaruh Persepsi Atas Metode Pembelajaran dan Minat Belajar Terhadap Pemahaman Konsep Matematika - Rahayu, Budi; Hasbullah; Tri Hapsari, Ambar (ALFARISI: Jurnal Pendidikan MIPA, 2026)
The purpose of this study was to determine whether students’ perceptions of teaching methods and their interest in learning influence their understanding of mathematical concepts. A survey method was employed, with a sample of 86 students. Data were collected by directly distributing questionnaires to the sample. Data analysis involved descriptive statistics—such as calculating the mean, median, mode, and standard deviation—and inferential statistics to determine coefficients. The study results revealed that: (1) there is a significant simultaneous influence of perceptions regarding teaching methods and interest in learning on the mathematical concept understanding of students at private Islamic junior high schools (MTs) in Bekasi Regency, evidenced by a significance value of 0.000 (< 0.05) and an F-statistic of 17.844; (2) there is a significant influence of students’ perceptions of teaching methods on their mathematical concept understanding, evidenced by a significance value of 0.000 (< 0.05) and a t-statistic of 4.665; and (3) there is a significant influence of interest in learning on mathematical concept understanding, evidenced by a significance value of 0.031 (< 0.05) and a t-statistic of 2.199.